Propafenone added to ibutilide increases conversion rates of persistent atrial fibrillation. Issue 5 (13th September 2005) - Korantzopoulos, P; Kolettis, T M; Papathanasiou, A; Naka, K K; Kolios, P; Leontaridis, I; Draganigos, A; Katsouras, C S; Goudevenos, J A
Abstract : Objective: To assess the effectiveness and safety of pharmacological conversion of persistent atrial fibrillation (AF) with a combined propafenone plus ibutilide regimen. Methods and results: 100 consecutive patients (66 men, mean (SD) age 65 (10) years) with persistent AF (mean (SD) duration 99 (92) days) admitted for elective pharmacological cardioversion were randomly assigned to treatment with either intravenous ibutilide (1 mg plus an additional 1 mg, if required; n = 51) or oral propafenone (600 mg) plus intravenous ibutilide at the same dose (n = 49). Success rates were 41.1% (21 of 51 patients) for ibutilide alone and 71.4% (35 of 49 patients) for propafenone plus ibutilide (p = 0.0044). However, cardioversion occurred earlier in the ibutilide alone group (55 (20) minutes) compared with the combination group (81 (32) minutes, p = 0.0019). A comparable increase in the QTc interval was observed in both groups but one case of sustained torsade de pointes, requiring electrical cardioversion, was observed in the propafenone plus ibutilide group. No other complications were noted during the hospitalisation period. Conclusion: Concurrent administration of propafenone plus ibutilide for pharmacological cardioversion of persistent AF is safe and more effective than ibutilide alone.